Development and validation of a measurement scale for the experience capability construct. (25th June 2020) - Ponsignon, Frédéric; Smith, Jeffery S.; Smart, Andi
Abstract : Purpose: This study aims to develop and empirically validate the concept of experience capability, which represents an organisation's ability to be adept at managing the customer experience. Organisations that build an experience capability develop an expertise in deploying a set of resources and routines to understand, evaluate and improve how they interact with customers across all the points of contact. Design/methodology/approach: A rigorous process was employed to identify, operationally define, evaluate and validate six dimensions reflecting experience capability. The dimensions were developed and validated using relevant literature, expert interviews, item-sorting techniques, a pilot survey and two surveys, providing a degree of certainty that the intellectual insights are generalisable. Findings: The experience capability concept is identified as comprising six dimensions that are informed by 27 measurement items. The six dimensions are employee training, employee empowerment, employee evaluation, experience performance management, cross-functional work and channel integration. The findings provide evidence suggesting that the multi-item measurement scale exhibits appropriate psychometric properties. Practical implications: The empirically validated 27-item measurement scale provides practitioners with an approach to evaluate and improve their organisation's experience capability. It permits both longitudinal comparisons of individual organisations and competitive benchmarking both within and across industry sectors. The approach alerts managers to the critical operational areas that should be measured and provides a structured method to pursue competitive advantage through customer experience capability. Originality/value: Developing valid and reliable measurement scales is an essential first step in effective theory-building. The paper proposes a theoretical foundation for the experience capability construct and validates a corresponding measurement scale. The scale was developed carefully to achieve the specificity required to undertake meaningful practitioner-centric assessment while maintaining relevance across sectorial contexts. The results complement existing customer-centric experience research by providing distinct intellectual insights from a practitioner perspective. The developed scale permits future intellectual investigation through capability comparisons both within and between companies in different industries/sectors.